Body without organs of Antonin Artaud in the transcendence of the logic of subjectivation. Cronotopies in «The Voice of the Moon» by Federico Fellini - Romero Tenorio, José Manuel; Buitrago Echeverry, Carolina; Díaz Téllez, Ángel Saúl (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
We propose an aesthetic theory based on a chronotopic threading of creative discourse that rethinks the constitution logic of the subject. We take as a thread the film The voice of the moon (La voce della Luna, 1990) by Federico Fellini, whose surrealism, far from supposing a random construction of a story, reveals a sophisticated narrative from the circumstantial (and not from the subject or the object). This is where we come together with the most radical theses of Antonin Artaud and his political project based on the theater of cruelty and the reification of the fragment-organ. We conclude with a plea for a vital narrative, which transcends the work, dissipates the position of the subject in it (what Jacques Derrida calls Forcener le subjectile) so that the meaning of humanity, in the tiny and fragmented, transpires.